Phytochemical Screening And Identified Bioactive Compounds of Leaf of Sarcochlamys Pulcherrima (ROXB.) Gaud By GC-MS - Pathak, Bhaskar; Kalita, Jogen C.; Bhuyan, Robin (Journal of Neonatal Surgery, 2025)
Sarcochlamys pulcherrima (Roxb.) Gaud. Commonly known as dogal tree in English. Rabha tribes it is called Fok xaak, as well as they consider as a sacred plant for their religious festival of Baikhyo. Sarcochlamys pulcherrima plant leaves are traditionally used as a natural medicine for various disorders and illness, as well as nutritional purposes. Objectives: The study was aimed to assess the phytochemical component and biological activity compounds of Sarcochlamys pulcherrima leaves extract that would support both the traditional and pharmaceutical uses of its leaves. Methods: The biologically active non-polar compounds are identified by GC-MS analysis and then, each of the extracts was subjected to qualitative phytochemical analysis and further subjected to a GC-MS instrument. Results: The result of the qualitative analysis of plant extracts has a wide range of active phytocompounds are found such as alkaloids, flavonoids, glycosides, saponins, steroids, reducing sugar, tannins and terpenoids. The biologically Gas chromatography and Mass spectroscopy (GC-MS) analysis screening shows that it has various biologically active compounds present in methanolic extract of leaf of Sarcochlamys pulcherrima. The GC-MS analysis, various phytochemical compounds were identified in leaf extract which have the properties of anti-inflammatory, anti-microbial, cyto-toxicity and anti-bacterial properties due to the presence of secondary metabolites in the methanolic extract of leaf. The identification of bioactive compounds is based on the retention time, peak area, molecular formula and probability. Therefore, Sarcochlamys pulcherrima (Roxb.) Gaud is recommended as a source of significant phytopharmaceutical value.